AIR's experience with 'drm dual channel transmission on single frequency' through shortwave transmitter - Rajendiran T.; Bhatia S. (My University, 2025)
Shortwave transmissions, which are the only way to provide radio signals to the listeners all across the world free of charge, face problems of fading, interference and distortion. However with digital radio, there is no such problem. As a result, most international broadcasters, all over the world, are moving to DRM digital systems on shortwave. Apart from audio quality, digital radio has numerous other advantages. The biggest advantage is that transmitters in analogue can broadcast only one programme at one frequency, while in the digital format we can broadcast three to four programmes (channels) on a single frequency and ensure excellent quality of all the channels. This paper gives a brief account of the experiment conducted by All India Radio on Dual Channel transmission using single frequency through a DRM shortwave transmitter.